P008 Methotrexate and baff interaction prevents immunisation against TNF-Α inhibitors by increasing adenosine and regulatory B-cells. (21st February 2018) - Bitoun, S; Nocturne, G; Ly, B; Krzysiek, R; Pruvost, A; Paoletti, A; Pascaud, J; Dönnes, P; Florence, K; Gleizes, A; Hincelin-Mery, A; Allez, M; et al.
Abstract : Introduction: TNFα inhibitors (TNFi), frequently used in patients with autoimmune diseases, can induce anti-drug antibodies (ADA) in one third of cases, leading to secondary resistance. Methotrexate (MTX) is known to decrease immunisation against TNFi. In BAFFtg mice, a model of autoimmune disease in which immunisation against biologic drugs is high, we investigated a new way of tolerization using a single course of MTX and we identified the mechanisms involved in this tolerization. Objectives: To assess the potential interaction between BAFF and tolerizaion induced by MTX. Methods: BAFFtg mice treated with TNFi with or without MTX were monitored for drug concentration and ADA. WT and BAFFtg mice were compared for B-Cell surface markers involved in MTX-related purinergic metabolism, adenosine production or B-regulatory cells (Bregs). Then, BAFF levels, MTX treatment and ADA were assessed in the human ABIRISK cohort of patients with chronic inflammatory diseases. Results: In BAFFtg but not in WT mice, a single course of MTX prevented immunisation against TNFi and maintained drug concentration for over 52 weeks. BAFFtg mice B-cells expressed more CD73 and CD39 leading to more adenosine production and to increase in Breg. MTX-induced tolerization was reversed in vivo using anti-CD73 antibodies. In patients treated with TNFi for chronic inflammatory diseases, high BAFF serum level was protective against ADA formation to TNFi only in patients co-treated with MTX but not in patients on TNFi monotherapy. Conclusions: This data supports an interaction between MTX and BAFF via increase in CD73 to prevent ADA formation in mice and humans. Treatment increasing CD73 could potentialize the role of MTX to prevent immunisation. Disclosure of interest: S. Bitoun: None declared, G. Nocturne: None declared, B. Ly: None declared, R. Krzysiek: None declared, A. Pruvost: None declared, A. Paoletti: None declared, J. Pascaud: None declared, P. Dönnes: None declared, K. Florence Employee of: GSK, A. Gleizes: None declared, A. Hincelin-Mery Employee of: Sanofi, M. Allez: None declared, S. Hacein Bey: None declared, M. Pallardy: None declared, X. Mariette: None declared